KEBERADAAN BANK TANAH DALAM PENGADAAN TANAH UNTUK PEMBANGUNAN - Hairani Mochtar (University of Merdeka Malang, 2013)
Construction realization always needed land, and it made land became commodity which made the price of itwent up whereas in construction for public interest, land deliverance was slow even pending. One of thesolutions to gain land for construction was by applying land bank especially public land bank which hadfunctions as land collector, and land management medium in exploiting and using land to be more productiveby gaining or buying land before there was a need so the price of it was cheap. Land supply in constructionrealization which always had a problem that caused physical construction in all fields at a standstill or evenpending was caused by improper regulation and economy and politic change, from democracy economy toneoliberalism capitalism economy. It made commodity land which triggered land liberalism. And the price ofland went up was caused by land speculator. One way to overcome the complexity of land supply problem forconstruction was by implementing land bank which had a function as land collector, as land protector to savesupply and for land exploitation as planned layout which had been legalized.